The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1021/acsami.5b00155
|View full text |Cite
|
Sign up to set email alerts
|

Creation of Reduced Graphene Oxide Based Field Effect Transistors and Their Utilization in the Detection and Discrimination of Nucleoside Triphosphates

Abstract: Two low-cost, micropatterned, solution-gated field effect transistors (modified FET and unmodified FET) based on reduced graphene oxide (RGO) were developed and used for detection and discrimination of nucleoside triphosphates (NTPs). The modified FET was realized by simple deposition of a positively charged bis-pyrenyl derivative, py-diIM-py, onto the conducting RGO strips of the unmodified FET. The electrical properties and sensing behaviors of the as-prepared devices were studied comprehensively. Electrical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 50 publications
0
8
1
Order By: Relevance
“…Usually it consists of the film and a couple of metallic contacts. In order to enhance sensitivity more complicated FET structure can be constructed [121]. For selective sensitivity the surface can be modified by catalyst particles or chemical agents to enhance charge transfer from detecting agent to GO layer.…”
Section: Sensors For Chemistry and Biologymentioning
confidence: 99%
“…Usually it consists of the film and a couple of metallic contacts. In order to enhance sensitivity more complicated FET structure can be constructed [121]. For selective sensitivity the surface can be modified by catalyst particles or chemical agents to enhance charge transfer from detecting agent to GO layer.…”
Section: Sensors For Chemistry and Biologymentioning
confidence: 99%
“…Reference electrodes made of Ag/AgCl represent a common choice since their use in electrolyte buffer is well calibrated. 103 Others have reported immersed gate electrodes made of silver 43,104,105 or platinum 106 wires. Coplanar gate electrodes are patterned on the substrate in a similar approach as for source and drain electrodes, using deposition of metals such as platinum, 55 silver 107 or gold.…”
Section: Substrate and Electrodesmentioning
confidence: 99%
“…Chang et al [258] also demonstrated that the large-area few-layer RGO films exhibit ambipolar charge transport characteristics in a bottom-gate FET architecture, which can be used as a phototransistor. Yu et al [259] showed that both the as-prepared RGO FET and FET with RGO modified by a bis-pyrenyl derivative, py-diIM-py, exhibit V-shaped ambipolar field effect behavior from p-type region to ntype region.…”
Section: Field-effect Transistors (Fets)mentioning
confidence: 99%
“…The detection limit of this RGO-based FET biosensor is around 0.2 ng/mL, which is among the best of reported carbon nanomaterial based protein sensors and can be further optimized by tuning the sensor structure. Besides, GO-based FETs with high sensitivity to other biomaterials were also reported, including the glucose with a limit of detection of 1 nM and a rapid response within 1 s [263], GTP and ATP with a detection limit as low as 400 nM [259], and matrilysin (MMP-7) with a limit of detection of 10 ng/mL (400 pM) [300]. sensitivity can be ascribed mainly to the electron transfer between the reduced GO and the adsorbed gaseous molecules of NO2 or NH3.…”
Section: Field-effect Transistors (Fets)mentioning
confidence: 99%